2021
DOI: 10.1021/jacs.0c13001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thiolate versus Alkoxide Ligands on the Stability of Crystallographically Characterized Mn(III)-Alkylperoxo Complexes

Abstract: The work described herein demonstrates the exquisite control that the inner coordination sphere of metalloenzymes and transition-metal complexes can have on reactivity. We report one of few crystallographically characterized Mn-peroxo complexes and show that the tight correlations between metrical and spectroscopic parameters, established previously by our group for thiolate-ligated RS-Mn(III)-OOR complexes, can be extended to include an alkoxide-ligated RO-Mn(III)-OOR complex. We show that the alkoxide-ligate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“… 16 Very recently, Kovacs et al reported a room-temperature stable Mn III –alkylperoxo complex supported by an alkoxide analogue of the N 4 S − ligands. 17 DFT computations for the [Mn III (OO t Bu)(N 4 O)] + and [Mn III (OO t Bu)(N 4 S)] + pair support the notion that the enhanced stability of the alkoxide-ligated complex arises from greater Lewis acidity of the Mn III center.…”
Section: Introductionmentioning
confidence: 73%
“… 16 Very recently, Kovacs et al reported a room-temperature stable Mn III –alkylperoxo complex supported by an alkoxide analogue of the N 4 S − ligands. 17 DFT computations for the [Mn III (OO t Bu)(N 4 O)] + and [Mn III (OO t Bu)(N 4 S)] + pair support the notion that the enhanced stability of the alkoxide-ligated complex arises from greater Lewis acidity of the Mn III center.…”
Section: Introductionmentioning
confidence: 73%
“…We note that the stoichiometric chemistry of Mn complexes with thiolate containing ligands and O 2 has been explored extensively by Kovacs and coworkers. [71][72][73][74][75] Upon exposure to dry air, both centers were oxidized by a single electron and a bridging hydroxide species was recovered. Mechanistic studies established that the dinuclear monothiol species united two separate reaction cycles, where either H 2 O 2 or H 2 O production was favored.…”
Section: Catalytic O 2 Reduction Mediated By Mnmentioning
confidence: 99%
“…21,47 We also recently showed that aliphatic thiolates help to promote peroxo O−O bond cleavage. 48,49 Very few well-characterized iron-superoxo compounds have been reported, 21,50−53 and of those reported, only two incorporate a thiolate in the coordination sphere 21,50 and only one cleaves strong C−H bonds. 21 We recently showed that aliphatic thiolate-ligated [Fe II (S 2…”
Section: ■ Introductionmentioning
confidence: 99%
“…Much of our understanding of the properties of heme and nonheme iron enzyme dioxygen intermediates such as Fe­(III)–superoxos, Fe­(III)–peroxos, and high-valent iron oxos comes from small-molecule chemistry. Only a small number of these are derived from O 2 , , and despite the key role of thiolates in a wide variety of nonheme iron enzymes, only a small number of these contain thiolates in the coordination sphere. ,,, Key properties unique to aliphatic thiolate (RS – or Cys-S – ) ligands include an increase in the potency of high-valent iron oxo intermediates and, as shown by our group, the potency of iron-superoxo compounds with respect to their ability to cleave strong C–H bonds. , We also recently showed that aliphatic thiolates help to promote peroxo O–O bond cleavage. , Very few well-characterized iron-superoxo compounds have been reported, , and of those reported, only two incorporate a thiolate in the coordination sphere , and only one cleaves strong C–H bonds . We recently showed that aliphatic thiolate-ligated [Fe II (S 2 Me2 N 3 (Pr,Pr))] ( 1 ) reacts with O 2 (Scheme ) to form an unprecedented example of an aliphatic thiolate-ligated iron superoxo intermediate, [Fe III (S 2 Me2 N 3 (Pr,Pr))­(O 2 )] ( 2 ), which is capable of cleaving strong C–H bonds (e.g., tetrahydrofuran (THF) (BDE­(C–H) = 92 kcal mol –1 )) at −73 °C with a k H / k D = 4.8 .…”
Section: Introductionmentioning
confidence: 99%